2013
DOI: 10.1007/s10787-013-0188-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of agmatine against d-galactosamine and lipopolysaccharide-induced fulminant hepatic failure in mice

Abstract: Fulminant hepatic failure (FHF) is a life-threatening syndrome characterized by massive hepatic necrosis and high mortality. There is no effective therapy for the disease other than liver transplantation. This study aimed to investigate the effect of agmatine, inducible nitric oxide synthase (iNOS) inhibitor, on D-galactosamine and lipopolysaccharide (GalN/LPS)-induced FHF in mice and explore its possible mechanism(s). Male Swiss albino mice were injected with a single dose agmatine (14 mg/kg, IP) 8 h prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…Agmatine has multiple roles in several biological processes 3435. In the present study, we found several lines of evidence indicating that agmatine can enhance NSC differentiation into neurons by modulating expression of let-7a .…”
Section: Discussionsupporting
confidence: 59%
“…Agmatine has multiple roles in several biological processes 3435. In the present study, we found several lines of evidence indicating that agmatine can enhance NSC differentiation into neurons by modulating expression of let-7a .…”
Section: Discussionsupporting
confidence: 59%
“…It is also known that AGM has hepatoprotective effects that may be related to its ability to suppress oxidative stress, NO synthesis and TNF-α production (El-Agamy et al 2014;Rushaidhi et al 2013). The beneficial effect of AGM could relate to the ability of AGM to inhibit iNOS or to block NMDA receptors and/or voltage-dependent Ca 2+ channels (Yang and Reis 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The blood and liver tissues were collected 8 h after LPS/GalN challenge for subsequent analysis. The chose of 8 h after LPS/GalN challenge were based on previous study [36]. …”
Section: Methodsmentioning
confidence: 99%